Population genetics of Galeorhinus galeus, Carcharhinus brachyurus and Rhinobatos annulatus- implications for regional fisheries and elasmobranch conservation - Bitalo, Daphne Nyachaki (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhDAgric)--Stellenbosch University, 2016.